2013
DOI: 10.1002/ijc.28535
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of allergy history and antibodies to specific varicella‐zoster virus proteins on glioma risk

Abstract: Glioma is the most common cancer of the central nervous system but with few confirmed risk factors. Glioma has been inversely associated with chicken pox, shingles, and seroreactivity to varicella virus (VZV), as well as to allergies and allergy-associated IgE. The role of antibody reactivity against individual VZV antigens has not been assessed. Ten VZV-related proteins, selected for high immunogenicity or known function, were synthesized and used as targets for antibody measurements in the sera of 143 glioma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 52 publications
0
10
0
4
Order By: Relevance
“…Findings from the previous literature, bolstered by those of our study, provide strong epidemiologic rationale for continued investigation of the potential role of chickenpox (or other manifestations of VZV infection) in glioma development [3,[8][9][10][11][12][13]. Future studies will need to account for the potential impact of the VZV vaccine, which was licensed in 1995 in the U.S. for use among children [2] (and therefore cannot be evaluated in the older population of the GICC).…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…Findings from the previous literature, bolstered by those of our study, provide strong epidemiologic rationale for continued investigation of the potential role of chickenpox (or other manifestations of VZV infection) in glioma development [3,[8][9][10][11][12][13]. Future studies will need to account for the potential impact of the VZV vaccine, which was licensed in 1995 in the U.S. for use among children [2] (and therefore cannot be evaluated in the older population of the GICC).…”
Section: Discussionmentioning
confidence: 68%
“…The majority of published studies on VZV infection and glioma risk are from the San Francisco Bay Area Adult Glioma Study (SFBAGS) series [8][9][10][11]13]. Using both self-reported and serologic (anti-VZV IgG) data to assess history of chickenpox, findings from this series have indicated that prior exposure to VZV is associated with an approximately 40% lower glioma risk [9][10][11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In animal models, pretreatment of GB with bortezomib has been shown to promote NK cell cytotoxicity and to inhibit tumor growth ultimately leading to prolonged survival [278]. Varicella zoster virus (VZV) is the only virus with negative correlation with GB [169,279]. NK cells represent a signi icant barrier to oncolytic herpes simplex virus therapy of GB [280].…”
Section: Nk Cells In Solid Tumorsmentioning
confidence: 99%
“…Other risk factors that are not discussed here have been investigated in relation to glioma risk, including but not limited to: Type 1 and type 2 diabetes, body mass index, birth weight, hypertension, height, birth weight, menarche (age at onset), menopause (age at onset), coffee/caffeine consumption, low-density lipoprotein cholesterol, insulin-like growth factor 1, insulin-like growth factor binding protein, triglycerides, high-density lipoprotein cholesterol, pesticide exposure, extremely low frequency magnetic fields, vitamin E, A and C levels ( Preston-Martin and Mack, 1991 ; Kaplan et al, 1997 ; Houben et al, 2004 ; Linos et al, 2007 ; Holick et al, 2010 ; Kabat et al, 2011 ; Little et al, 2013 ; Malerba et al, 2013 ; Lee et al, 2014 ; Andersen et al, 2015 ; Li et al, 2015 ; Zhou et al, 2015 ; Seliger et al, 2016a , b ; Zhao et al, 2016 ; Wiedmann et al, 2017 ).…”
Section: Risk Factors For Gliomamentioning
confidence: 99%